The Role of Government Policies and Strategies Behind the Shrinking Urban Core in an Expanding City Region: The Case of Izmir - Özatagan, Güldem; Eraydın, Ayda (Taylor and Francis Ltd., 2014)
Over the last few decades, the term urban shrinkage has come to be accepted as a valid concept in international academic circles, and has gradually gained importance, with its causes the subject of well-documented discussion. While previous discussions of urban shrinkage have directed attention to cities shrinking as a whole, recent research started to recognize the case of shrinkage in growing cities and regions. As such, recent discussions of urban shrinkage indicate that patterns of shrinkage vary considerably from city to city, and from sub-region to sub-region, with the importance of local dynamics in responding to changing economic pressures given much consideration. Recent studies have tended to disregard the role of government policies and strategies put in place to facilitate the adaptation of the urban economies to the new conditions. Taking Izmir as an example, being a fast-growing metropolitan region in Turkey, this paper presents evidence of government policies and strategies aimed at enhancing the development of peripheral areas that have led to shrinkage of the metropolitan core. This paper focuses on this experience and discusses its implications.
Keywords: Development strategy; Metropolitan area; Peripheral region; Urban economy; Izmir